2020
DOI: 10.1093/asj/sjaa221
|View full text |Cite
|
Sign up to set email alerts
|

Spare Roof Technique Versus Component Dorsal Hump Reduction: A Randomized Prospective Study in 250 Primary Rhinoplasties, Aesthetic and Functional Outcomes

Abstract: Background The majority of Caucasian aesthetic rhinoplasty patients complains about a noticeable hump in the profile view. Based on the integrity of the middle vault, there are two ways to dehump a nose: the structured technique and the preservation technique. Objectives We compared the aesthetical and functional outcomes of two techniques utilized for reduction rhinoplasty. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…34 A modified osseocartilaginous preservation technique (''spare roof technique'') has shown to have better aesthetic and functional results over component dorsal hump reduction. 39 We also have ongoing studies that demonstrate equivalent, if not superior, aesthetic outcomes with DPR techniques. In addition, we have shown that DPR can be combined with anterior septal reconstruction in cases of severe caudal septal deviation.…”
Section: Discussionmentioning
confidence: 98%
“…34 A modified osseocartilaginous preservation technique (''spare roof technique'') has shown to have better aesthetic and functional results over component dorsal hump reduction. 39 We also have ongoing studies that demonstrate equivalent, if not superior, aesthetic outcomes with DPR techniques. In addition, we have shown that DPR can be combined with anterior septal reconstruction in cases of severe caudal septal deviation.…”
Section: Discussionmentioning
confidence: 98%
“…The benefits were first demonstrated in a pilot study by reporting a significant improvement in UQ postoperative scores of 100 consecutive patients treated with this technique 11 . This finding was later strengthened by conducting a comparative study that included 250 subjects in which a significantly higher improvement in UQ scores was observed in patients undergoing Spare Roof Technique compared to patients treated with traditional Component Dorsal Reduction 12 . This work was presented as part of the thesis for his doctorate, which was granted by Universidade do Porto in 2020.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 In a strict sense, the spare roof technique (SRT) does not fall under the category of complete dorsal osseocartilaginous preservation rhinoplasty (DPR), as it involves obligatory removal of the bony cap, osteotomies as well as routinely recommended dorsal camouflage with diced or sliced cartilage grafts. 4 Still, the concept of preservation of the midvault is central to both DPR and SRT.…”
mentioning
confidence: 99%
“…The SRT, as originally described, involves removal of the dorsal and lateral keystone areas, as well as osteotomies, much like standard component reduction. 4 The advantage of the technique is that the strength of the dome of the T-shaped middle-vault structure (septum and upper lateral cartilages, which some argue are a single entity) is preserved. That is, the subdorsal septal resection does not violate the ''dome'' of the midvault.…”
mentioning
confidence: 99%
See 1 more Smart Citation